Editorial: Microbial interaction with banana: Mechanisms, symbiosis, and integrated diseases control - Zheng, Sijun; Hu, Huigang; Li, Yunfeng; Chen, Jian; Li, Xundong; Bai, Tingting (Frontiers Media, 2024)
Editorial: Microbial interaction with banana: Mechanisms, symbiosis, and integrated diseases control